Water rights and the processes of negotiation among irrigators in West Shewa Zone: the case of Indris Irrigation Scheme in Toke Kutaye District [Ethiopia]. - Zeleke, T.; Awulachew, Seleshi Bekele (2010)
This paper scrutinizes water rights and the processes of negotiation among irrigators diverting water fr01n Indris Scheme. The scheme marked three phases in its historical development. 'Multiple water use rights reflecting the theoretical orientation of legal pluralism have co-existed governing the behaviors of users. Conflicts have been attributed to institutional malfunctioning, weak observance on water right rules and increasing statistics of users. Negotiations have been initiated to settle conflicts. The formulation of water guidelines stipulating specific irrigation water use entitlements, awareness butlding, promotion of negotiated approaches, and enforcement of customary rules constituted the dimensions that seek meticulous consideration in prospect.